Impaired interactions of ataxin-3 with protein complexes reveals their specific structure and functions in SCA3 Ki150 model - Piasecki, Piotr; Wiatr, Kalina; Ruszkowski, Milosz; Marczak, Łukasz; Trottier, Yvon; Figiel, Maciej (Frontiers in Molecular Neuroscience, 2023)
Spinocerebellar ataxia type 3 (SCA3/MJD) is a neurodegenerative disease caused by CAG expansion in mutant ATXN3 gene. The resulting PolyQ tract in mutant ataxin-3 protein is toxic to neurons and currently no effective treatment exists. Function of both normal and mutant ataxin-3 is pleiotropic by their interactions and the influence on protein level. Our new preclinical Ki150 model with over 150 CAG/Q in ataxin-3 has robust aggregates indicating the presence of a process that enhances the interaction between proteins. Interactions in large complexes may resemble the real-life inclusion interactions and was never examined before for mutant and normal ataxin-3 and in homozygous mouse model with long polyQ tract. We fractionated ataxin-3-positive large complexes and independently we pulled-down ataxin-3 from brain lysates, and both were followed by proteomics. Among others, mutant ataxin-3 abnormally interacted with subunits of large complexes such as Cct5 and 6, Tcp1, and Camk2a and Camk2b. Surprisingly, the complexes exhibit circular molecular structure which may be linked to the process of aggregates formation where annular aggregates are intermediate stage to fibrils which may indicate novel ataxin-3 mode of interactions. The protein complexes were involved in transport of mitochondria in axons which was confirmed by altered motility of mitochondria along SCA3 Ki150 neurites.